In vitro and in vivo activity of meglumine antimoniate produced at Farmanguinhos-Fiocruz, Brazil, against Leishmania (Leishmania) amazonensis, L (L.) chagasi and L (Viannia) braziliensis - Eliane de Morais-Teixeira; Alcione S de Carvalho; Jorge CS da Costa; Silvio L Duarte; Jorge S Mendonça; Núbia Boechat; Ana Rabello (Memorias do Instituto Oswaldo Cruz, 2008)
The leishmanicidal activity of four batches of meglumine antimoniate, produced in Farmanguinhos-Fiocruz, Brazil (TAMs), was assessed and compared to Glucantime®-Aventis Pharma Ltda. Using the amastigote-like in vitro model, the active concentrations of Sb v varied from 10µg/ml to 300 µg/ml for L. (L.) chagasi and from 50µg/ml to 300µg/ml for L. (L.) amazonensis, with no statistically significant differences among the four batches of TAMs and Glucantime®. The inhibitory concentrations (IC50) determined by the amastigote-infected macrophage model for TAM01/03 and Glucantime® were, respectively: 26.3µg/ml and 127.6µg/ml for L. chagasi, 15.4µg /ml and 22.9µg/ml for L. amazonensis, and 12.1µg/ml and 24.2µg/ml for L. (V.) braziliensis. The activities of the four batches of TAMs were confirmed in an in vivo model by assessing, during eight weeks skin lesions caused by L. braziliensis in hamster that were treated with 20mg Sb v/Kg/day for 30 consecutive days. The meglumine antimoniate produced by Farmanguinhos was as effective as the reference drug, Glucantime®-Aventis, against three species of Leishmania that are of medical importance in Brazil.